Negative Responses toward ÐœÐ¾ÑÐºÐ²Ð° - Moskva Song by Timati in 2019: Russian Citizens' Protest towards Their Government - Elfira, Mina; Prinandatama, Dzulfiqar Patriot (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
This study discusses the negative response of the people of Russia and Moscow to the song Moskva by Timati, the song with the most dislikes in Russia on the video provider site, Youtube. The writer analyzes the data by using Reception theory by Stuart Hall in analyzing people's response, and propaganda theory by Jowett and O'Donnell in finding the causes of protests over this song. The method used in this research is descriptive analysis, literature study, and interview techniques to obtain the required response data. The results of this study are that the many protests over this song are caused by propaganda elements contained in the song lyrics. The lyrics contains lines and verses, viewed from the lens of propaganda, that are heavily political and leans towards a biased belief of one political spectrum. Other than lyrical aspects, the visualization of the song through its music video also contains propagandistic trait. This is manifested through the abundance of skyscrapers in Moscow shown in the music video which signify the urbanized part of the city, leaving the undesired part enclosed. The combination of the song's internality and responses results in a comprehensive outlook for the song.